1979
DOI: 10.1037/0096-1523.5.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Moving attention through visual space.

Abstract: Several experiments have shown that attention as measured by simple reaction time to luminance increments can be shifted in the visual field while the eyes are kept in a fixed position. The shift of attention appears to take place within 50 msec following a cue indicating the most likely position of the target. The present study reports that these shifts of attention can be time locked to a central cue. Moreover, they show that a probe event located between the cue and the target receives maximal facilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
258
5
6

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(297 citation statements)
references
References 5 publications
28
258
5
6
Order By: Relevance
“…Some researchers (e.g. Shulman et al, 1979;Tsal, 1983) have presented results compatible with this view of attention. Others (e.g.…”
Section: Methodsmentioning
confidence: 55%
“…Some researchers (e.g. Shulman et al, 1979;Tsal, 1983) have presented results compatible with this view of attention. Others (e.g.…”
Section: Methodsmentioning
confidence: 55%
“…6 It is clear that the general framework for viewing detection experiments outlined in this article is quite con-6 While this article has been in press much of the work outlined here has been accomplished. For a discussion of movements of covert attention see Shulman, Remington, and McLean (1979). A broader treatment of the relationship between overt and covert attention movements may be found in Posner (1980).…”
Section: Resultsmentioning
confidence: 99%
“…First, there is evidence to suggest that attention tends to travel in an analog manner and that locations in the path of this movement are attended and locations off the path are not attended (e.g., O'Donnell & Pratt, 1996;Pratt & Abrams, 1994;Shulman, Remington, & McLean, 1979;Tipper, Lortie, & Baylis, 1992). For example, O'Donnell and Pratt found that cuing a more eccentric location yielded inhibition at a less eccentric target location only if the less eccentric target location was along the path that attention traveled to reach the cued location.…”
Section: Response Latencies At Uncued Locationsmentioning
confidence: 99%